Plasmodium falciparum: sensitivity in vivo to chloroquine, pyrimethamine/sulfadoxine and mefloquine in western Myanmar. - Smithuis, F; Monti, F; Grundl, M; Oo, A; Kyaw, T; Phe, O; White, N (1997)
In Rakhine State, on the western border of Myanmar, the efficacy of chloroquine (CQ) and pyrimethamine/ sulfadoxine (PS), the current treatments for uncomplicated Plasmodium falciparum malaria in this area, was evaluated in an open comparative study of 289 patients, stratified prospectively into 3 age groups. Chloroquine treatment was associated with more rapid clinical recovery (P = 0.03), but the overall cure rates were worse than for PS treatment; failure to clear parasitaemia or recrudescence within 14 d occurred in 72% (102/141) of cases treated with CQ compared to 47% (69/148) of those who received PS (P < 0.0001, adjusted for age). Failure rates at day 28 increased to 82% (116/141) in the CQ group and 67% (99/148) in the PS group (P = 0.003). The risk of treatment failure was significantly higher in children under 15 years old than in adults for both CQ (relative risk [RR] = 2.6; 95% confidence interval [95% CI] 1.3-5.2) and PS (RR = 2.2; 95% CI 1.4-3.3). Mefloquine (15 mg base/kg) proved to be highly effective as a treatment for CQ and PS resistant P. falciparum; only 2 of 75 patients (3%) had early treatment failures (< or = day 7), and the overall failure rate by day 42 was 7%. There is a very high level of chloroquine and PS resistance in P.falciparum on the western border of Myanmar, but mefloquine was effective in the area.